Adulteration of Pomegranate Molasses With Sugar Syrups: Application of FTIR-ATR Spectroscopy and Chemometrics - Kilinc, Gizem Simge; Uncu, Oguz; Eren, Ismail; Bagdatlioglu, Neriman (Elsevier, 2025)
In this study, it was aimed to determine the adulteration ratio of pomegranate molasses (PM) with sugar syrups by using FTIR spectroscopy based upon chemometrics. With this intention, 34 pure PM samples were supplied from local manufacturers and adulterated with high fructose corn syrup (HFCS), glucose-fructose syrup (GFS) and beet sugar syrup (BSS) in varying ratios (5-50 %, w/w). Authentic and adulterated PM samples were analyzed in the range of 4000 and 400 cm(-1) wavenumber by FTIR spectroscopy. PCA was applied as a pretreatment for classification and regression analysis to select the spectral region and data reduction. Whereby the DD-SIMCA models were created using this information. The adulterated and authentic samples were classified correctly by the developed DD-SIMCA models. In the calibration and prediction model of DD-SIMCA, authentic and adulterated PM samples were correctly classified with high sensitivity (>= 0.91) and specificity (>= 0.94), and a clear distinction was observed with high efficiency (>= 0.94). Adulteration rates in PM samples were determined by PLS-R analysis. The correlation coefficients (R-2 >= 0.98) of models were also found quite high. As a consequence, FTIR spectroscopy in conjunction with chemometric approaches could be applied as a quick, dependable, non-destructive, and environmentally friendly tool for categorizing, distinguishing, and quantifying adulteration rates in PM samples.
Keywords: Pomegranate Molasses; Ftir Spectroscopy; Adulteration; Chemometrics; DD-SIMCA; PLS-R